Emotion concept in perception of facial expressions: Effects of emotion-label words and emotion-laden words. (9th September 2022) - Li, Wanyue; Xu, Qiang; Liu, Shen; Yu, Linwei; Yang, Yaping; Zhang, Lin; He, Xianyou
Abstract: Emotion perception, the ability to detect and categorize the emotions of others, is an important component of social competence. The basic emotion theory and constructed emotion theory remain controversial over the role of emotional semantic information in the processing of facial expressions. In the present study, in order to explore the mechanism of emotional semantic information in different processing stages of facial expressions, we used the ERPs to investigate the effects of emotion-label words (e.g., happy, disgusted) and emotion-laden words (e.g., flower, maggot) on the perception of happy and disgusted faces. The results showed that disgusted faces were more susceptible to emotion words, and there were differences between word types and consistency conditions in the N170 component. More importantly, disgusted faces showed a significant N400 effect in the emotion-label words condition, that is, the amplitude in the emotion inconsistent condition was negative compared with that in the emotion consistent condition. The processing of happy faces was not significantly affected by the emotional information of words, and no significant effects related to consistency or to word types were found. These results found that disgusted faces exhibited emotional semantic conflict in the inconsistent emotion-label words condition, suggesting that emotion words moderated the perception of disgusted faces, supporting the hypothesis that emotional semantic information influenced the perception of facial expressions. Highlights: Compared with emotion-laden words, emotion-label words had a more significant effect on facial expression perception. Compared with happy faces, disgusted faces were more dependent on the emotional semantic information of words. Disgusted faces showed a significant N400 effect in the emotion-label words condition.